2015
DOI: 10.1007/s10658-015-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryphonectria parasitica isolates of the same vegetative compatibility type display different rates of transfer of CHV1 hypovirus

Abstract: Hypovirulent strains of the chestnut blight fungus Cryphonectria parasitica have not been registered in the autonomous region of Castilla y León (Spain), except in the province of León. In this laboratory-based study, we analyzed the rates of horizontal transmission of hypovirus CHV1 subtype F1, isolated from chestnut stands in León. We tested the conversion capacity of the six vegetative compatibility (vc) types of C. parasitica isolates most commonly distributed in Castilla y León (EU1, EU11, EU12, EU66, CL5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…A high rate of transmission was expected, as mitoviruses FcMV1 and FcMV2-2 are associated with the mitochondria that the offspring inherit from the parents [17]. The high transmission rates of mycoviruses are consistent with those reported for asexual spores of other fungal species such as Ustilaginoidea virens [26] and Epichloë festucae [27] whereas for other pathogens variable rates of virus transmission were observed, e.g., Heterobasidion annosum [13] and CHV1 hypovirus infecting Chryphonectria parasitica [28][29][30]. In some species, usually ascomycetes, there appear to be barriers to the transmission of viruses during sexual reproduction and the formation of sexual spores [27].…”
Section: Discussionsupporting
confidence: 76%
“…A high rate of transmission was expected, as mitoviruses FcMV1 and FcMV2-2 are associated with the mitochondria that the offspring inherit from the parents [17]. The high transmission rates of mycoviruses are consistent with those reported for asexual spores of other fungal species such as Ustilaginoidea virens [26] and Epichloë festucae [27] whereas for other pathogens variable rates of virus transmission were observed, e.g., Heterobasidion annosum [13] and CHV1 hypovirus infecting Chryphonectria parasitica [28][29][30]. In some species, usually ascomycetes, there appear to be barriers to the transmission of viruses during sexual reproduction and the formation of sexual spores [27].…”
Section: Discussionsupporting
confidence: 76%
“…dianthi isolates. In addition to the vic genes that regulate hyphal anastomosis, the host genetic background has been shown to affect horizontal virus transmission (Cortesi et al, 2001 ; Choi et al, 2012 ; Zamora et al, 2015 ). Although all race 2 isolates are in VCG 0021, we have evidence that some isolates in a same VCG show a reduced compatibility, that is, they can anastomose with a few but not all the isolates in the VCG (Gómez-Lama Cabanás and Pérez-Artés, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that vegetative compatibility is not an impossible obstacle to overcome. For example, Hamid et al [ 59 ] found a novel mycovirus in S. sclerotiorum that was identified and described as the first +ssRNA mycovirus capable of spreading across the vegetative compatibility barrier [ 55 , 60 , 61 ]. Brusini and Robin found that although the transmission of CHV1 between vic strains was difficult in plates, it was much easier when the strains were inoculated in chestnuts [ 62 ].…”
Section: Mycoviruses: a Natural Source Of Fungal Hypovirulencementioning
confidence: 99%